Simulating photoacoustic waves from individual nanoparticle of various shapes using k-Wave - Verawaty (2016)
Photoacoustic imaging techniques have been widely discussed for their potential applications in the biomedical field. Current attempts at understanding the photoacoustic signal characteristic of various shapes of nanoparticles is mostly performed through numerical simulations. They require complex mathematical formulations prior to the simulation. Moreover, computationally they are expensive. In this work, k-Wave simulation toolbox was used to simulate the photoacoustic signal generated from various shapes of nanoparticles. Seven shapes of nanoparticles are simulated here: sphere, cylinder, hollow cylinder, cube, hollow cube, triangle, and nano star. A point sensor (ultrasound detector) is used to detect the photoacoustic signal. The simulated photoacoustic signal is presented both in time and frequency domain and used for understanding the impact of the various shapes on the photoacoustic signal characteristics. The detector was placed at various locations to see how the photoacoustic signal characteristics changes with transducer positions. There is a distinguishable signature of the nanoparticle shape on the frequency spectrum of the photoacoustic waves. The simulation time for each nano particle is as short as 40 s, which is significant improvement over previously reported simulation time of few hours using analytical methods.